Using augmented reality to learn indigenous language - Asni Tahir; Nurul Farahin Hikmatullah Darwisal; Siti Hasnah Tanalol; Jetol Bolongkikit; Mohd Shamrie Sainin; Norazlina Khamis (Pusat e-pembelajaran, UMS, 2022)
The internet combined with the capabilities of smartphones is transforming the teaching and learning paradigm and practises. To realise the benefits, an educational Dusun language learning mobile application is developed to help learners learn the language. This paper presents the development of a mobile application using augmented reality for learning the Dusun language, which is a language of native people in Sabah. It is an attempt to support the limited availability of digital learning resources for this language and to preserve the language that is not spoken by the younger generation. The Mobile Dusun application is an Android-based application developed as a tool to easily learn the basic vocabulary of Dusun language. An experiment was conducted with N=31 students at Universiti Malaysia Sabah to investigate the usability of the mobile Dusun language learning application. This study uses a research and development approach by applying the ADDIE model which consists of Analysis, Design, Development, Implementation and Evaluation. In general, the initial test results showed positive feedback that the mobile application can be used to support language learning.